Getting the MOST out of follow-up: a randomized controlled trial comparing 3 monthly nurse led follow-up via telehealth, including monitoring CA125 and patient reported outcomes using the MOST (Measure of Ovarian Symptoms and Treatment concerns) with routine clinic based or telehealth follow-up, after completion of first line chemotherapy in patients with epithelial ovarian cancer. Issue 4 (22nd September 2021) - Cohen, Paul A; Webb, Penelope M; King, Madeleine; Obermair, Andreas; Gebski, Val; Butow, Phyllis; Morton, Rachael; Lawson, Wanda; Yates, Patsy; Campbell, Rachel; Meniawy, Tarek; McMullen, Michelle; et al.
Abstract : Background: Physical symptoms, anxiety, depression, fear of recurrence, sexual dysfunction, and social withdrawal are common in women after treatment for ovarian cancer. Most patients would like and need help dealing with these symptoms. The traditional model of follow-up care is unstructured and largely focused on diagnosing recurrent disease, and most oncologists lack skills to identify and manage psychosocial issues. No high quality prospective clinical trials have been conducted to determine the optimal follow-up regimen or the cost effectiveness of ovarian cancer surveillance strategies. Primary Objective(s): To assess emotional wellbeing, acceptability, safety, and cost effectiveness of nurse led follow-up via telehealth for women with ovarian cancer following completion of primary treatment. Study Hypothesis: We hypothesize that compared with routine clinic based follow-up, nurse led follow-up via telehealth, including serum CA125 monitoring and completion of a patient reported outcome instrument, the Measure of Ovarian Symptoms and Treatment concerns-Surveillance (MOST-S26), will improve emotional wellbeing in women with ovarian cancer; be feasible, safe, acceptable, and not delay the time to diagnosis of recurrent disease; will result in greater patient satisfaction; will identify more patients with psychological distress, lead to better care, and improved psychological outcomes; and be cost-effective. Trial Design: Phase II multicenter randomized trial comparing 3 monthly nurse led telehealth consultations that include serum CA125 monitoring and completion of the MOST-S26, with routine clinic based follow-up. The allocation ratio will be 1:1. Major Inclusion/Exclusion Criteria: Eligible patients will be women with high grade epithelial ovarian cancer who have normalized serum CA125 (to <35 kU/L) at completion of first line chemotherapy. Primary Endpoint(s): Emotional wellbeing at 12 months. Sample Size: 150 patients. Estimated Dates for Completing Accrual and Presenting Results: July 2023. Results expected in 2025, 24 months after the last participant is enrolled. Trial Registration: ACTRN12620000332921